Sağlık Turizmi Kapsamında Medikal (Tıbbi) Turizm Potansiyelinin ve Sürdürülebilirliğinin Kayseri Örneğinde Değerlendirilmesi - Ramazan Koca (Coğrafi Bilimler Dergisi)
Medical tourism, which is included in health tourism, is a type of tourism that is rapidly increasing in its development and prevalence globally due to the diversification of personal care services and the increase in different and appropriate treatment options. The aim of the research is to evaluate the medical tourism potential and sustainability of Kayseri based on the views of relevant stakeholders. The research was conducted based on the interview technique in qualitative research method. In this context, face-to-face in-depth interviews were conducted with 20 stakeholders in the field. The interviews were coded and analyzed using Nvivo 10 qualitative data analysis software. As a result of the research, appropriate treatment opportunities, sufficient health centers and specialist physicians increase the medical potential of the area. In addition, it was concluded that the realization of technology-based treatments, patient satisfaction, combining tourism activities with medical treatment and preparing tour packages are effective on the sustainability of medical tourism. In addition, it is revealed that the development of medical tourism is related to economic, social and cultural development and its sustainability should be ensured as it affects the development of many sectors.